Systematic reviews of effectiveness of Public Health practice (Italian Journal of Public Health, 2006)
Background: Public Health is the main discipline involved in the prevention of avoidable deaths. Toimplement interventions aimed at eliminating causes of death, and to take decisions based on evidence ofeffectiveness, research summaries are needed.Methods: To discuss the critical points for synthesizing the evidence on the effectiveness of public healthinterventions, the inconsistencies between the results produced by different epidemiological study designsand the methodological issues related to the quality of the summaries are underlined.Results: The Randomized Controlled Trial is recognized as the best study design for the assessment of theeffectiveness of clinical practices; however, the integration of the results from non-randomized andrandomized interventions has been suggested recently. In particular this involves Public Health, where therandomization of individuals is often impossible, and interventions are administered at different levels(individual, group, population).Conclusions: Systematic reviews are not common in Public Health. Methodological tools to write rigoroussummaries of the evidence from public health interventions, taking into account all possible biases, appearto be a priority.
Keywords: public health; systematic reviews; evidence-based practice; prevention; avoidable mortality